Retention of microplastics in sediments of urban and highway stormwater retention ponds - Liu, Fan; Vianello, Alvise; Vollertsen, Jes (Environmental pollution (1987), 2019)
Urban and highway surfaces discharge polluted runoff during storm events. To mitigate environmental risks, stormwater retention ponds are commonly constructed to treat the runoff water. This study is the first to quantify the retention of microplastics in the sediments of such ponds. It applied state-of-art FTIR-methods to analyse the composition, size, shape, and mass of microplastics in the range 10–2000 μm. Seven ponds serving four land uses were investigated, and the results are related to catchment characteristics, sediment organic matter content, and hydraulic loading. We have not found a correlation between the microplastics abundance, polymer composition, size distribution and the land use in the catchment, as well as the sediment organic matter content. Both the highest (127,986 items kg−1; 28,732 μg kg−1) and the lowest (1511 items kg−1; 115 μg kg−1) accumulation of microplastics were found in the sediments of ponds serving industrial areas. There was, however, a correlation to the hydraulic loading of the ponds, where the sediments of the highest-loaded ponds held the most microplastics. This study shows that sediments in stormwater retention ponds can trap some of the microplastics and prevent them from being transported downstream. These systems need to be considered when assessing the fate of microplastics from urban and highway areas. [Display omitted] •A first assessment of microplastics in the sediments of stormwater retention ponds.•Ponds experiencing a higher hydraulic load accumulated more microplastics.•Most identified microplastics were in the size range 10–250 μm.•Polypropylene was the dominating polymer, in terms of both particle number and mass. The study demonstrated that stormwater retention pond is able to trap microplastics from urban and highway runoff in sediments, and the retention is correlated to the hydraulic loading of the pond.